Studi Literatur: Potensi Daya Bunuh Tanaman Keluarga Asteraceae Terhadap Larva Aedes Aegypti: Literature Review: The Killing Power Potency of Asteraceae Plants Againts Aedes Aegypti Larvae - Muhammad Noer Perdana Sakti Widodo; Indria Augustina; Elsa Trinovita; Ratna Widayati; Arif Rahman Jabal (Jurnal Surya Medika (JSM), 2023)
Aedes aegypti is the main transmitter of dengue hemorrhagic fever which is an important health problem in Indonesia and the world. The main vector of dengue hemorrhagic fever (DHF) is the Aedes aegypti mosquito which originated from Africa and discovered in Indonesia in 1968 in Surabaya. DHF continues to spread to all 472 districts or cities in 34 provinces in Indonesia. Data on dengue cases recorded until the 49th week of 2020 were 95,893 cases and 661 cases of death. Biological control using natural ingredients which is Asteraceae family plants that have larvicidal activity is one of the methode to prevent transmission and reproduction of the main vector. The object of this study is to know the potential of Asteraceae family plants as larvicides against Aedes aegypti. The method of this study is systematic review. The data sources used are secondary data obtained from Google Scholar. The keywords are Asteraceae, Aedes aegypti and larvicide. There are 17 literatures which fulfill the criteria. Synthesis of data is using SPIDER. The result of this study is, from 17 international and national journals reviewed, there were 9 (52,95%) journals shows that Asteraceae family plants have low potential to become Aedes aegypti larvicides and 8 (47,05%) journals shows that Asteraceae family plant have the potential to become Aedes aegypti larvicides, this is based on the LC50 value >1000ppm which indicates that the larvicidal activity is low. Asteraceae family plants have low potential to become Aedes aegypti larvicides.